Agricultural residues for cellulolytic enzyme production by Aspergillus niger: effects of pretreatment - Salihu, Aliyu; Abbas, Olagunju; Sallau, Abdullahi Balarabe; Alam, Md Zahangir (Springer Berlin Heidelberg, 2015)
Different agricultural residues were considered in this study for their ability to support cellulolytic enzyme production by Aspergillus niger. A total of eleven agricultural residues including finger millet hulls, sorghum hulls, soybean hulls, groundnut husk, banana peels, corn stalk, cassava peels, sugarcane bagasse, saw dust, rice straw and sheanut cake were subjected to three pretreatment (acid, alkali and oxidative) methods. All the residues supported the growth and production of cellulases by A. niger after 96 h of incubation. Maximum cellulase production was found in alkali-treated soybean hulls with CMCase, FPase and beta-glucosidase yields of 9.91 +/- 0.04, 6.20 +/- 0.13 and 5.69 +/- 0.29 U/g, respectively. Further studies in assessing the potential of soybean hulls are being considered to optimize the medium composition and process parameters for enhanced cellulase production.